Review of the Oriental leafhopper genus Parafagocyba Kuoh & Hu (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China - Yan, Bin; Yang, Mao-Fa (Zootaxa, 2017)
The genus Parafagocyba is reviewed. Three new species are described and illustrated: P. membrana sp. nov., P. longa sp. nov. and P. striata sp. nov.. Illustrations, a key and checklist of species are provided. The type specimens are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).